Work-Family Conflict & Burnout in the face of a Pandemic as moderated by Sensory Processing Sensitivity and Social Support - Ndlovu, Valerie (University of the Witwatersrand, Johannesburg, 2024)
Remote working has quickly become a norm in organisations in response to the COVID-19 global pandemic. This shift may have been a tough transition on some individuals as work and family spheres have been obscured by remote working where one environment is used for both leisure, domestic and professional reasons. A quantitative, non- experimental, correlational, cross- sectional study (N = 136) was conducted with employed South African participants using online self- report questionnaires. Correlation results showed a significant relationship between Work-Family Conflict (WFC) and burnout subscales, but not Family-Work Conflict (FWC) and burnout. Hierarchical Moderated regression was used to assess the data and showed that Sensory- Processing Sensitivity and Social Support did not moderate the relationship between WFC and burnout. The results show that females are more burnt out than males and as people get older, the less burnt out they are. Individuals experienced financial and fear of the unknown challenges due to the pandemic. This study offers a contribution to Human Resources on employee wellbeing and post- COVID-19 functioning.
A research report submitted in fulfillment of the requirements for the Master’s (Industrial/Organisational Psychology), In the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; burnout; work-family conflict; sensory processing sensitivity; COVID-19; social support; SDG-3: Good health and well-being